A person-situation perspective of informal learning: the role of supervisor feedback environment. Issue 1 (24th February 2021) - Zia, Muhammad Qamar; Bashir, Muhammad Adnan; Mangi, Riaz Ahmed; Shamsi, Aamir Feroz
Abstract : Purpose: Based on trait activation theory, the purpose of the present study is to explore the relationship between the antecedents and outcomes of informal learning with the moderating effect of supervisor feedback environment (SFE) in small- and medium-sized enterprises (SMEs). Design/methodology/approach: Data ( n = 388) were gathered from middle managers of Pakistan's SME sector by following the purposive sampling technique. The proposed model was examined by means of structural equation modeling analysis with AMOS 24. Findings: The study results delineate that middle managers with high-level self-efficacy and motivation to learn more actively participate in informal learning activities. The study also found that the SFE is a strong contextual moderator between the nexus of personal factors and informal learning. In addition, informal learning also has significant and positive effect on work engagement. Practical implications: Human resource practitioners and organizational leaders of small businesses can use informal learning to improve employees' skills and knowledge with less cost. For instance, management should use different strategies to enhance the effectiveness of informal learning by providing SFE. Originality/value: There are numerous recent calls for research to ascertain the interaction of individual, contextual factors and outcomes of informal learning. The study addresses these voids by empirically examining antecedents and outcomes of informal learning simultaneously through the person–situation interaction perspective. It demonstrates that informal learning at the workplace becomes more effective in SFE.